Changes in children respiratory infections pre and post COVID-19 pandemic - Yuanyuan Yue; Yuanyuan Yue; Dan Wu; Dan Wu; Qian Zeng; Qian Zeng; Yurong Li; Yurong Li; Chun Yang; Chun Yang; Xin Lv; Xin Lv; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundNon-pharmaceutical interventions (NPIs) implemented during the COVID-19 pandemic had a significant impact on the prevalence of various acute respiratory infections (ARIs) pathogens.MethodsWe collected 337,310 real-time PCR results for 13 pathogens from clinical samples between January 2018 and January 2024 to assess the changes of ARIs among children before and after the COVID-19 pandemic.ResultsA variety of ARIs pathogens, including Influenza A (Flu A), Influenza B (Flu B), Adenovirus (ADV), Rhinovirus (RhV), and Respiratory Syncytial Virus (RSV), as well as co-infecting bacterial such as Klebsiella pneumoniae (KPN), Pseudomonas aeruginosa (PAE), Streptococcus pneumoniae (SP), Haemophilus influenzae (HI), and Legionella pneumophila (LP), reached a peak positive rate at the age of 3. The susceptible age of Mycoplasma pneumoniae (MP) was from 3 to 7 years old. Compared to the pre-COVID pandemic period, the positive rates of Flu A, MP, ADV, SP, HI, Staphylococcus aureus (SA) and KPN decreased during the COVID-19 pandemic. And the positive rates of Flu B and PAE increased. Compared to the period during the COVID-19 pandemic, the positive rates of Flu A, ADV, RSV, RhV, SP, HI, KPN, PAE and SA were increased after the pandemic. Conversely, the positive rates of MP, Flu B, and Parainfluenza virus (PIV) decreased.ConclusionsThe implementation of NPIs interrupted the circulation of ARIs pathogens. However, release of NPIs and the reduced baseline of population immunity, may contribute to a resurgence of ARIs pathogens among children.